Electrodeposition of V-VI Nanowires and Their Thermoelectric Properties - Manzano, Cristina V.; Martin-Gonzalez, Marisol (Frontiers in Chemistry, 2019)
Nanostructuration is an intensive field of research due to the appearance of interesting properties at the nanoscale. For instance, in thermoelectricity, the most outstanding improvements obtained lately are due to phenomena that appears when nanostructuring different materials. The thermoelectric effect is the direct conversion from temperature gradients into electricity and vice versa. When going to low dimensions, for instance, in thermoelectric nanowires, the transport properties of phonons are modified when compared to those of the bulk, leading to a higher thermoelectric figure of merit z. In more detail, this review tries to compile some of the landmarks in the electrodeposition of Bi2Te3-based nanowires. We will focus on the achievements using different templates, electrolytes and deposition modes. We will also summarize the measurements performed in those nanowires and the main conclusions that can be extracted from the published works. Finally, an update of nanowire-based thermoelectric generators are also included.